Cordyceps militaris Modulates Intestinal Barrier Function and Gut Microbiota in a Pig Model - Zheng, Hongmei; Cao, Haigang; Zhang, Deming; Huang, Jiahe; Li, Jinshu; Wang, Shaoying; Lu, Junfeng; Li, Xiao; Yang, Gongshe; Shi, Xin’e (Frontiers in Microbiology, 2022)
This study investigated the effects of Cordyceps militaris (CM) on intestinal barrier function and gut microbiota in a pig model. A total of 160 pigs were randomly allocated to either a control group (fed the basal diet) or a CM group (fed the basal diet supplemented with 300 mg/kg CM). CM improved intestinal morphology and increased the numbers of goblet cells and intraepithelial lymphocytes. CM also elevated the expression of zona occluden-1, claudin-1, mucin-2 and secretory immunoglobulin A. Furthermore, the mucosal levels of pro-inflammatory cytokines were downregulated while the levels of anti-inflammatory cytokines were upregulated in the CM group. Mechanistically, CM downregulated the expression of key proteins of the TLR4/MyD88/NF-κB signaling pathway. Moreover, CM altered the colonic microbial composition and increased the concentrations of acetate and butyrate. In conclusion, CM can modulate the intestinal barrier function and gut microbiota, which may provide a new strategy for improving intestinal health.